COVID-19 and the HIV continuum in people living with HIV enrolled in Collaborating Consortium of Cohorts Producing NIDA Opportunities (C3PNO) cohorts. (1st December 2022) - Lesko, Catherine R.; Keruly, Jeanne C.; Moore, Richard D.; Shen, Nicola M.; Pytell, Jarratt D.; Lau, Bryan; Fojo, Anthony T.; Mehta, Shruti H.; Kipke, Michele; Baum, Marianna K.; Shoptaw, Steven; Gorbach, Pamina M.; et al.
Abstract: Background: The COVID-19 pandemic disrupted the normal delivery of HIV care, altered social support networks, and caused economic insecurity. People with HIV (PWH) are vulnerable to such disruptions, particularly if they have a history of substance use. We describe engagement in care and adherence to antiretroviral therapy (ART) for PWH during the pandemic. Methods: From May 2020 to February 2021, 773 PWH enrolled in 6 existing cohorts completed 1495 surveys about substance use and engagement in HIV care during the COVID-19 pandemic. We described the prevalence and correlates of having missed a visit with an HIV provider in the past month and having missed a dose of ART in the past week. Results: Thirteen percent of people missed an HIV visit in the past month. Missing a visit was associated with unstable housing, food insecurity, anxiety, low resiliency, disruptions to mental health care, and substance use including cigarette smoking, hazardous alcohol use, cocaine, and cannabis use. Nineteen percent of people reported missing at least one dose of ART in the week prior to their survey. Missing a dose of ART was associated with being a man, low resiliency, disruptions to mental health care, cigarette smoking, hazardous alcohol use, cocaine, and cannabis use, and experiencing disruptions to substance use treatment. Conclusions: Social determinants of health, substance use, and disruptions to mental health and substance use treatment were associated with poorer engagement in HIV care. Close attention to continuity of care during times of social disruption is especially critical for PWH. Highlights: During the COVID-19 pandemic, missing an HIV visit or a dose of ART was common. Social determinants of health were associated with missing an HIV visit. Substance use was associated with missing an HIV visit or ART dose. Disrupted mental health treatment was tied to a missed HIV visit or ART dose.